Construction Of Student's Political Rights About Sexy Killers Showing - Fatmawati Fatmawati; Siti Maizul Habibah (JED (Jurnal Etika Demokrasi), 2021)
The purpose of this study was to describe the impact of the presentation of Sexy Killers on the Political Rights of Students of the Faculty of Social Sciences and Law at the State University of Surabaya. The screening of the Sexy Killers film through social media has an impact on the political rights of students where the political rights of these students will determine the political choices made by students. The political choices of students themselves are influenced by the political views of students regarding the Sexy Killers film and the political attitudes of students by giving or not giving voting rights during the 2019 presidential election as a result of the Sexy Killers film. The focus in this research is student suffrage. The method used is a qualitative approach with a case study design. The result of this research is that there is an impact of changing students 'perspectives on politics and students' perspectives on their political choices as a result of the screening of the Sexy Killers film, although many students are pessimistic and disappointed with their political choices so that students choose what is considered good in terms of achievement and track record candidates so that there is also no political choice for golput, although feelings of pessimism and disappointment persist. Tujuan penelitian ini adalah untuk mendeskripsikan dampak penyajian Sexy Killers terhadap Hak Politik Mahasiswa Fakultas Ilmu Sosial dan Hukum Universitas Negeri Surabaya. Pemutaran film Sexy Killers melalui media sosial berdampak pada hak politik mahasiswa dimana hak politik mahasiswa tersebut akan menentukan pilihan politik yang dibuat mahasiswa. Pilihan politik mahasiswa sendiri dipengaruhi oleh pandangan politik mahasiswa terhadap film Sexy Killers dan sikap politik mahasiswa dengan memberikan atau tidak memberikan hak suara pada pemilihan presiden 2019 akibat film Sexy Killers. Fokus dalam penelitian ini adalah hak pilih siswa. Metode yang digunakan adalah pendekatan kualitatif dengan desain studi kasus. Hasil dari penelitian ini adalah terdapat dampak dari perubahan cara pandang mahasiswa terhadap politik dan cara pandang mahasiswa terhadap pilihan politiknya sebagai akibat dari pemutaran film Sexy Killers, walaupun banyak mahasiswa yang pesimis dan kecewa dengan pilihan politiknya sehingga agar mahasiswa memilih yang dinilai baik dari sisi prestasi dan rekam jejak calon sehingga juga tidak ada pilihan politik untuk golput, meski perasaan pesimis dan kecewa tetap ada.